Testing and Debugging Quantum Circuits - Metwalli, Sara Ayman; Van Meter, Rodney (IEEE transactions on quantum engineering, 2024)
This article introduces a process framework for debugging quantum circuits, focusing on three distinct types of circuit blocks: amplitude-permutation, phase-modulation, and amplitude-redistribution circuit blocks. Our research addresses the critical need for specialized debugging approaches tailored to the unique properties of each circuit type. For amplitude-permutation circuits, we propose techniques to correct amplitude-permutations mimicking classical operations. In phase-modulation circuits, our proposed strategy targets the precise calibration of phase alterations essential for quantum computations. The most complex amplitude-redistribution circuits demand advanced methods to adjust probability amplitudes. This research bridges a vital gap in current methodologies and lays the groundwork for future advancements in quantum circuit debugging. Our contributions are twofold: we present a comprehensive unit testing tool (Cirquo) and debugging approaches tailored to the unique demands of quantum computing, and we provide empirical evidence of its effectiveness in optimizing quantum circuit performance. This work is a crucial step toward realizing robust quantum computing systems and their applications in various domains.